The Concept Promtoional Mix Max Pictures in Promotional Strategy Film Dilan 1991 - Joshua Eka Saputra; Denny Antyo Hartanto; Soekma Yeni Astuti (Program Studi Film dan Televisi Universitas Jember, 2023)
Film distribution is an activity in the form of promotion with the aim to bring the film together with the audience. This is the basis of this research with the object of the film Dilan 1991. The problem of the research is how the concept of reference mix by Max Pictures in conducting the promotion strategy of the film Dilan 1991. The purpose of this research is to find out the concept of mixing reference by Max Pictures in conducting the film Dilan 1991 promotion strategy. This study uses qualitative research methods and theoretical approaches to marketing and promotion strategies. Data collection techniques used in this study were interviews with film Dilan 1991 producers and the film Dilan 1991 promotion team, observation of reporting on film Dilan 1991 in the mass media, and literature studies on marketing and promotion strategies. The results of this study are expected to be able to reveal how the concept of the promotional mix reference by Max Pictures in carrying out the promotion strategy of the film Dilan 1991. This research resulted in 2 discussions including a marketing strategy and a promotional mix reference in the film Dilan 1991.